Cumulative Sulfate Loads Shift Porewater to Sulfidic Conditions in Freshwater Wetland Sediment - Johnson, Nathan W. (Environ Toxicol Chem, 2019)
It is well established that sulfide can be toxic to rooted aquatic plants. However, a detailed description of the effects of cumulative sulfate loads on sulfide and iron (Fe) porewater geochemistry, plant exposure, and ecological response is lacking. Over 4 yr, we experimentally manipulated sulfate loads to self‐perpetuating wild rice (Zizania palustris) populations and monitored increases in the ratio of sulfur (S) to Fe in sediment across a range of sulfide loading rates driven by overlying water sulfate. Because natural settings are complicated by ongoing Fe and S loads from surface and groundwater, this experimental setting provides a tractable system to describe the impacts of increased S loading on Fe–S porewater geochemistry. In the experimental mesocosms, the rate of sulfide accumulation in bulk sediment increased linearly with overlying water sulfate concentration up to 300 µg‐SO(4) cm(–3). Seedling survival at the beginning of the annual life cycle and seed mass and maturation at the end of the annual life cycle all decreased at porewater sulfide concentrations between 0.4 and 0.7 µg cm(–3). Changes to porewater sulfide, plant emergence, and plant nutrient uptake during seed production were closely related to the ratio of S to Fe in sediment. A mass balance analysis showed that porewater sulfide remained a small and relatively transient phase compared to sulfate in the overlying water and Fe in the sediment solid phase. The results illuminate the evolution of the geochemical setting and timescales over which 4 yr of cumulative sulfate loading resulted in a wholesale shift from Fe‐dominated to sulfide‐dominated porewater chemistry. This shift was accompanied by detrimental effects to, and eventual extirpation of, self‐perpetuating wild rice populations. Environ Toxicol Chem 2019;38:1231–1244. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.